2019
DOI: 10.3390/v11121138
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Capsid Proteins Impact Transduction Efficiency of Haploid Adeno-Associated Virus Vectors

Abstract: Our previous studies have demonstrated that haploid AAV vectors made from capsids of two different serotypes induced high transduction and prevented serotype-specific antibody binding. In this study, we explored the transduction efficiency of several haploid viruses, which were made from the VP1/VP2 of one serotype and VP3 of another compatible serotype. After systemic injection of 2 × 1010 vg of AAV vectors into mice, the haploid AAV vectors, composed of VP1/VP2 from serotypes 8 or 9, and VP3 from AAV2, displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Chai et al. 177 explored the transduction efficiency of several haploid viruses, which were made from the VP1/VP2 of one serotype and VP3 of another compatible serotype. The haploid AAV vectors, composed of VP1/VP2 from serotypes 8 or 9, and VP3 from AAV2, displayed an increased liver transduction compared with those of AAV2 vectors, while those with VP1/VP2 from serotypes 8 or 9 and VP3 from AAV3 achieved higher transductions in multiple tissue types compared with those of AAV3 vectors.…”
Section: Aav Capsidsmentioning
confidence: 99%
“…Chai et al. 177 explored the transduction efficiency of several haploid viruses, which were made from the VP1/VP2 of one serotype and VP3 of another compatible serotype. The haploid AAV vectors, composed of VP1/VP2 from serotypes 8 or 9, and VP3 from AAV2, displayed an increased liver transduction compared with those of AAV2 vectors, while those with VP1/VP2 from serotypes 8 or 9 and VP3 from AAV3 achieved higher transductions in multiple tissue types compared with those of AAV3 vectors.…”
Section: Aav Capsidsmentioning
confidence: 99%
“…AAV capsid monomers from different plasmid sources can also form “mosaic” rAAV particles with altered transduction efficiency. Mosaic rAAV are typically avoided for current gene therapy approaches [ 96 ], but researchers continue to identify mosaic AAV capsids with unique biochemical and transduction properties [ 97 , 98 , 99 , 100 , 101 ].…”
Section: Aav Capsid Modification Strategiesmentioning
confidence: 99%
“…28 Moreover, we recently demonstrated that polyploid rAAV vectors, generated from the cotransfection of AAV helper plasmids of different serotypes or mutants, are able to enhance AAV transduction in the liver and muscle and escape the pre-existing Nabs. 28,29 Since polyploid vectors contain subunits from different AAV capsids, they potentially acquire advantages from parental serotypes or mutants for enhanced AAV transduction. Additional approaches without capsid modification involve proteins and peptides, which have attracted considerable attention for a wide range of applications in the fields of gene therapy and biotechnology.…”
Section: Introductionmentioning
confidence: 99%